Effect of heavy metals on the energy metabolism in the brackish water flea Diaphanosoma celebensis - Jiyoon Lee; Min Jeong Jeon; Eun-Ji Won; Je-won Yoo; Young-Mi Lee (Ecotoxicology and Environmental Safety, 2023)
Heavy metals such as lead (Pb), cadmium (Cd), and arsenic (As) are of great concern in aquatic ecosystems because of their global distribution, persistence, and biomagnification via the food web. They can induce the expression of cellular protective systems (e.g., detoxification enzymes and antioxidant enzymes) to protect organisms from oxidative stress, which is a high-energy-consuming process. Thus, energy reserves (e.g., glycogen, lipids, and proteins) are utilized to maintain metabolic homeostasis. Although a few studies have suggested that heavy metal stress can modulate the metabolic cycle in crustaceans, information on changes in energy metabolism under metal pollution remains lacking in planktonic crustaceans. In the present study, the activity of digestive enzymes (amylase, trypsin, and lipase) and the contents of energy storage molecules (glycogen, lipid, and protein) were examined in the brackish water flea Diaphanosoma celebensis exposed to Cd, Pb, and As for 48 h. Transcriptional modulation of the three AMP-activated protein kinase (AMPK) and metabolic pathway-related genes was further investigated. Amylase activity was highly increased in all heavy metal-exposed groups, whereas trypsin activity was reduced in Cd- and As-exposed groups. While glycogen content was increased in all exposed groups in a concentration-dependent manner, lipid content was reduced at higher concentrations of heavy metals. The expression of AMPKs and metabolic pathway-related genes was distinct among heavy metals. In particular, Cd activated the transcription of AMPK-, glucose/lipid metabolism-, and protein synthesis-related genes. Our findings indicate that Cd can disrupt energy metabolism, and may be a potent metabolic toxicant in D. celebensis. This study provides insights into the molecular mode of action of heavy metal pollution on the energy metabolism in planktonic crustaceans.